Partial discharge detection using rogowski coil sensor on medium voltage aerial bundle cable / Norhidayu Rameli … [et al.] - Rameli, Norhidayu; Abd. Halim, Huzainie Shafi; Nor Azli, Muhd. Irfan; Anthony, Tashia Marie; Pangah @ Pa’at, Mohd Azraei; Ibrahim, Muhammad Faiz; Nor Arifin, Nur Amira (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
It is well known that the internal partial discharge (PD) are small electric sparks that occurred due to defect in power cable insulation. This will be lead to premature failure of cable which consequently interrupt the supply on the distribution lines. In this paper, the results of internal partial discharge detected by rogowski coil (RC) sensor were presented. The RC sensors were designed, fabricated and tested in the laboratory with varying high frequency sinusoidal and impulse signals. An artificial PD defect was also created inside a straight through joint (STJ), medium voltage aerial bundle cable (MVABC) to generate PD signals. PD testing data in the laboratory were collected and analysed. Results indicates that the RC sensors able to detects injected continuos sinusoidal signal at lower frequencies ranging from 0.5 MHz to 10 MHz. The detected PD signal generated from artificial PD defect from RC sensor were found to be slightly higher amplitude as compared to commercial PD sensor, High Frequency Current Transformer (HFCT). Thus findings shows that the RC sensor able to be used as sensor to detect the internal partial discharge at MVABC specifically at STJs.